Ellagic acid prevents kidney injury and oxidative damage via regulation of Nrf-2/NF-?B signaling in carbon tetrachloride induced rats - Aslan, Abdullah; Gok, Ozlem; Beyaz, Seda; Agca, Can Ali; Erman, Orhan; Zerek, Aykut (Springer, 2020)
Phytochemicals, bioactive food compounds, found in plants have been described as protective agents against renal injury. This work was planned to evaluate the effects of EA on anti-oxidative and anti-inflammation pathways in kidney damage induced with carbon tetrachloride. In this study, experimental animals (n = 36, 8 weeks old rats) were divided into 4 groups as follows: 1) Control group 2) EA group (10 mg/kg body weight) 3) CCl4 group (1.5 ml/kg, body weight) 4) EA + CCl4 group. The potentially protective effect of EA on kidney damage exposed by CCl4 in rats were evaluated. EA administration protects CCl4 induced kidney damage against oxidative stress through its antioxidant protection. Treatment of EA significantly reduced lipid peroxidation and improved glutathione and catalase enzyme activity. Recently studies showed that EA activated caspase-3 and nuclear transcription factor erythroid 2 related factor driven antioxidant signal pathway and protected the kidney against damage induced by oxidative stress. Furthermore, EA also markedly decreased the level of cyclooxygenase-2, the vascular endothelial growth factor and tumor necrosis factor-alpha and suppressed the protein synthesis of nuclear factor-kappa-B. This study reveals that EA has kidney protective effect against CCl4 induced oxidative damage and inflammation. [GRAPHICS] .
Keywords: Carbon tetrachloride; COX-2; Ellagic acid; Kidney; NF-kappa B; Nrf-2; VEGF